PERANCANGAN ATRIBUT BRAND MOBIL LISTRIK INSTITUT TEKNOLOGI NASIONAL - Isnaini, Wiwi; Meiralarasari, Della (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Electric cars are vehicles without oil fuel, with electricity from batteries as its sole power source to ignite and to move. The research and design for EV has been developed since 180 years ago in the United States. However, until today, the acknowledgment for EV as mass-produced cars are still obstructed by some restrictions from the government and the public itself. There are perceptual belief that EVs are just concept cars and still products-on-trials, hence considered unfit for public use. Brand attribute design for electric vehicle made by Institut Teknologi Nasional are related to the creation for the brand identity itself. The naming created, logo, color, and essence for the brand identity will be percieved as the identity and persona by the people around Itenas in order to make a good impression towards Electric Cars in Indonesia. Through the Itenas EV brand attribute design, we want to create a perception that electric vehicle is on the same level with Internal Combustion engine (ICe) cars. Equal in speed, strength, durability, mobility, all that’s different is the cleaner, renewable energy source. Preferably in the future, society, government, and automotive industries will be more consenting to EV development and creation as an environmentally friendly means of transportation.